Bloom's Taxonomy Student Persona Responses to Blended Learning Methods Employing the Metaverse and Flipped Classroom Tools - Fotis Kilipiris; Spyros Avdimiotis; Evangelos Christou; Andreanna Tragouda; Ioannis Konstantinidis (MDPI AG, 2024)
The paper aims to identify and analyze the correlation between student personality types and the use of metaverse and flipped classroom blended learning methods (BLMs) and tools by formulating a series of research hypotheses. Using Bloom's Taxonomy, the most influential and standard theory of learning in the education cognitive field and toward this objective, the authors extracted the personality types of students and employed a mixed-methods research methodology JASP software (v.0.17.1) involving both qualitative and quantitative tools. The qualitative component involved direct observation of synchronous classroom teaching to students, while the quantitative aspect utilized structured questionnaires administered to 634 students of the International Hellenic University enrolled to attend the "Human Resource Management" course. The acquired qualitative data were processed using (a) network analysis JASP software (v.0.17.1) software in order to address the student personas through nodes, connections, and centralities and (b) structural equation software in order to identify the correlations between types of students and the variables of the metaverse and flipped classroom methods. The findings reveal that the four types of students identified have a direct and strong correlation with the use of flipped classroom and metaverse teaching methods.